This preview shows page 1. Sign up to view the full content.
Unformatted text preview: y = f ( k ) = Ak 7. MP K = f ( k ) = A k -1 8. Solow growth model I k t +1-k t = s Ak -k At the steady state s Ak = k Golden rule f ( k ss ) = 9. Solow growth model II k t +1-k t = s Ak -( + n ) k At the steady state s Ak = ( + n ) k 10. Solow growth model III k t +1-k t = s Ak -( + n + g ) k At the steady state s Ak = ( + n + g ) k...
View Full Document
This note was uploaded on 12/06/2010 for the course ECON 3020 taught by Professor Williamson during the Spring '10 term at FSU.
- Spring '10